(untitled) (Academia Journal of Medicine, 2020)
Background: Cardiovascular disease (CVD) is the leading cause of death in the developed world. The present study was conducted to assess correlation of plasma 25-Hydroxy-Vitamin D level with angiographic severity in coronary artery disease. Subjects and Methods: The present study was conducted on 120 patients of CAD. Group I were cases and group II were control. Hypertension, type II diabetes mellitus status, smoking etc. was recorded. 2 ml of blood sample was taken from all patients and measurement of 25(OH) vit D levels was performed. Results: The mean BMI in group I was 24.6 kg/m2and 24.8 kg/m2in group II, smoking habit was seen in 78 in group I and 34 in group II, hypertension was seen in 65 in group I and 26 in group II, diabetes was seen in 52 in group I and 30 in group II, alcoholism in 36 in group I and 10 in group II, dyslipidemia was seen in 48 in group I and 15 in group II. The mean 25 (OH) vitamin D in group I was 15.1 ng/ml and 19.6 ng/ml in group II. The difference was significant (P< 0.05). Maximum dyslipidemia (80.5%) patients had low vitamin D level followed by DM, smoking, BMI, alcoholism and alcoholism. There was no correlation between risk factors and vitamin D deficiency (P> 0.05). Conclusion: Authors found that in cases, vitamin D level was lowered as compared to control, however, there was no correlation between risk factors and CAD.